Effect of Additives on the Solubility and Dissolution of Piroxicam From Prepared Hard Gelatin Capsule - B. H. Al-Khedairy, Eman (Iraqi Journal of Pharmaceutical Sciences, 2017)
Piroxicam is a non-steroidal anti-inflammatory drug (NSAID) used in the treatment of musculo-skeletal and joint disorders. The problem with this drug is its poor solubility in water and hence poor bioavailability after oral administration. In order to improve its solubility and dissolution behavior, hydrophilic additives such as starch, lactose, superdisintegrants including crospovidone (C.P), cross carmellose sodium (CCS), and sodium starch glycolate (SSG) were physically dry mixed with the drug by simple trituration. The improvement in the solubility in 0.1 N HCl was obtained as the amount of starch or lactose increased in the physical mixture, while for superdisintegrants, they further improve the solubility when they are present in small amount and the best improvement was gained with SSG. To study the effect of these additives on the dissolution of the drug, piroxicam capsules were prepared by simple trituration of the drug with starch or lactose or combination of lactose: starch (2:1)by weight with or with out the presence of SSG. The dissolution profiles of these preparations were analyzed using similarity factor f2. Best results were obtained when the drug was triturated with starch and SSG or with acombinaton of lactose: starch (2:1) by weight with SSG . The dissolution profiles of these preparations were similar to that of the marketed Feldene Â® Pfizer 20 mg capsules with f2 74.6 and 80.37 respectively.Key words: Piroxicam, hydrophilic additives, superdisintegrant